Literature Circles and Jam Board: Interactive Ways to Comprehend Young Adult Literature - Rahmasari, Brigitta Septarini; Chasanatun, Tri Wahyuni (ELT-Lectura, 2024)
The purposes of the study are to describe the use of Literature Circles in the classroom using jam board media and to know the students’ responses to Young Adult Literature (YAL) using jam board. This study is qualitative research. The data collection method is observation and interview. Using a jam board, the researcher observes the use of literature circles in the classroom. Meanwhile, the researcher interviews the teacher and the students about their perception of the use of literature circles in the classroom using a jam board. Data analysis uses three steps, namely, data reduction, data displays, and drawing conclusions. The participants are 20 students of secondary school. The result shows that there are four roles in literature circles, namely, discussion leader, summarizer, question writer, word wizard, culture collector, and passage master. The students’ responses show that they are active in reading class because Jam Board is interesting media. They also could understand the text well since they work in groups and have their own roles. In addition to addressing the requirements of many students and providing them with responsibility and participation in the class, literature circles can be a useful instrument for increasing motivation by appealing to their reading interests because the literary text is frequently chosen by the group from a selection of adequately leveled options offered by the teacher.